Effectiveness of The Early Start Denver Model for Children with Autism: A Narrative Review and Experiences for Viet Nam - Thi, Thao Do; Anh, Thu Nguyen Thi; Thi, Nho Hoang; Thi, Tan Nguyen (Journal of Ecohumanism, 2024)
Early intervention for children with autism is crucial for their development and quality of life. Different early intervention models exist, including the Early Start Denver Model, which has scientific evidence and is included in Vietnam's Guidance Document on Diagnosis and Intervention for Children with autism spectrum disorders. Therefore, quantitative research design and descriptive statistics methodologies are used in the study to review the Denver early intervention model's effectiveness in treating children with autism worldwide and bring lessons learned for application in Vietnam. This narrative review analyses 16 scientific articles conducted in an international database. Research results show that the Early Start Denver Model is efficacious in improving core defects in children with autism, such as social skills, communication skills, and repetitive behaviors,…; using the Early Start Denver Model will improve parent-child interactions, reducing stress for parents during the parenting process. The findings also indicate lessons for applying the Early Start Denver Model for children with autism in Vietnam, considering factors like regional culture, educational facilities, and learning materials; motor skills and imitation skills should be combined with other therapies for better effectiveness.